Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/ped.13658
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid non‐pleocytosis in pediatric enteroviral meningitis: Large‐scale review

Abstract: CSF non-pleocytosis in childhood EVM was frequently observed, especially in young infants, regardless of season. We propose that CSF PCR testing for enterovirus can be helpful to recognize EVM in children with CSF non-pleocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Studying its sensitivity and specificity in actual clinical practice has been limited by the relatively low prevalence of positive bacterial results. In this study, there were multiple positive ME panel results without corresponding pleocytosis; however, studies have revealed viral and bacterial meningitis can lack pleocytosis, [14][15][16] thus making it difficult to fully interpret these results without additional testing. Additionally, HHV-6 results may remain positive, indicating a previous infection but not accounting for the acute illness.…”
Section: Discussionmentioning
confidence: 63%
“…Studying its sensitivity and specificity in actual clinical practice has been limited by the relatively low prevalence of positive bacterial results. In this study, there were multiple positive ME panel results without corresponding pleocytosis; however, studies have revealed viral and bacterial meningitis can lack pleocytosis, [14][15][16] thus making it difficult to fully interpret these results without additional testing. Additionally, HHV-6 results may remain positive, indicating a previous infection but not accounting for the acute illness.…”
Section: Discussionmentioning
confidence: 63%
“…С возрастом прослойка детей, имеющих антитела к циркулирующим на данной территории штаммам энтеровирусов увеличивается. Так, к первому году жизни порядка 50 % детей серопозитивны к наиболее распространенным серотипам энтеровирусов [6,7]. В первые дни инфицирования возбудитель в большом количестве выделяется из слизистых оболочек зева пациента, обнаруживается в крови, моче, носоглотке и фекалиях за несколько дней до появления клинических симптомов.…”
Section: Discussionunclassified
“…The proportion of patients with CSF non-pleocytosis in the case of enteroviral meningitis was approximately 30% of infants < 2 months of age in New Zealand [13] and in Missouri (USA) [14], and 31% in Pennsylvania (USA) [15]. In Korea, approximately 28% of infants < 3 months of age [16], 63.3% of neonates, and 38.3% of young infants aged 29 to 56 days [8] had CSF non-pleocytosis in enteroviral meningitis. Mulford et al [17] reported that 30% of infants < 2 months of age with enteroviral meningitis did not have pleocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that sufficient time may be needed for CSF pleocytosis to develop. In other words, in the early stages of central nervous system infections, results may indicate non-pleocytosis if sufficient time has not passed to allow pleocytosis to develop [8,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation